Multiple Rumors. - Librandi-Rocha, Marília (Luso-Brazilian Review, 2016)
This article aims to contribute to a renewed vocabulary in literary analysis, in particular with relation to studies focused on translation, multilingualism, oral cultures, and sound studies in fictional prose. Through an analysis of João Guimarães Rosa’s novella “O recado do morro” (1956), the study suggests the inclusion of two untranslatable words: recado and conconversa. The former, a Portuguese word that means “message,” “rumor,” and “warning,” simultaneously, refers to an imagined pre-babelic moment when nature “speaks.” The latter refers to a post-babelic moment, when the multiplicity of languages converses through translation in search of a shared meaning among linguistic differences.